Standardisasi Ekstrak Khaya (Khaya anthotheca) Sebagai Antikanker Payudara MCF-7 (Michigan Cancer Foundation-7) - Parwaz Setaviani; Nani Suryani; Zahra Khaerul Kamila; Siti Amaliya; Eneng Elda Ernawati; Tarso Rudiana; Arini Khaerunnisa (Jurnal Farmasi Indonesia, 2024)
Cancer is the second non-communicable disease that causes the largest number of deaths after cardiovascular disease. The chemical compounds contained in the Khaya anthotheca plant and which have anticancer activity include methyl angolensate, 7-deacetylhivorin, grandifolione, gedunin, , obacunone and Cathecin. This research aims to determine the standardization of extracts and determine anticancer activity against MCF-7 breast cancer cells. The method used in this research is standardization of specific and non-specific parameters, and cytotoxic testing using Prestoblue. The results of extract standardization of specific parameters have values ​​for soluble essence in water and ethanol of 4.68% and 5.80% (meeting the requirements). Non-specific parameters drying loss 0.739%, ash content 8.02%, microbial contamination 0 colonies, lead (Pb) 0.2976 mg/kg, cadmium (Cd) ≤0.001 mg/kg (qualified) and IC₅₀ value of anticancer activity breast MCF-7 from Khaya anthoteca extract was 194.20 µg/mL in the medium/moderate category